Nanometer material and application of feeding tank thereof in white spirit aging
By using nanomaterials and their feeding tanks in the aging of liquor, the problems of time-consuming, difficult to control and limited effects of traditional liquor natural aging methods are solved, and the rapid, stable and efficient aging of liquor is achieved to meet market demand and consumer expectations.
Patent Information
- Application Number
- CN202411553466.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-02
- Publication Date
- 2025-02-28
AI Technical Summary
The natural aging methods of traditional liquor are time-consuming, difficult to control and limited in effect, and cannot meet the rapidly growing market demand and consumers' demand for diversified liquor products.
Using nanomaterials and their specially designed feeding tanks, the rapid aging of liquor is achieved by fully contacting the nanomaterials with liquor, adsorption and catalyzing chemical reactions. The composition of nanomaterials includes silica, nanotitanium dioxide, nano aluminosilicate, etc. By optimizing the structure and parameters of the feeding tank, the contact time, temperature and pressure of the nanomaterials and liquor are controlled.
Through the adsorption, catalysis and diffusion of nanomaterials, the aging process of liquor is significantly accelerated, the purity and aroma concentration of liquor are improved, and the quality stability and the satisfaction of market demand are achieved, while providing a stable working environment and the reuse of nanomaterials.
Smart Images

Figure CN119529969A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of liquor aging, and in particular to application of a nano material and a feeding tank thereof in liquor aging. Background Art
[0002] In the field of liquor brewing, aging is a crucial link, which has a decisive influence on the quality and taste of liquor. Traditional liquor aging mainly relies on natural storage, allowing liquor to be stored in a specific environment for a long time, so that the various components in it undergo slow physical and chemical changes, thereby achieving a mellow taste and rich aroma. However, this natural aging method has many disadvantages.
[0003] First, the natural aging process is extremely time-consuming. It usually takes several years or even decades for liquor to complete aging, which not only takes up a lot of storage space, but also seriously affects the production cycle and market supply of liquor. For liquor production companies, long aging means a backlog of funds and low production efficiency, which cannot meet the rapidly growing market demand.
[0004] Secondly, the effect of natural aging is difficult to control. Due to the large changes in factors such as temperature and humidity in the natural environment, different batches of liquor may be affected to varying degrees during the aging process, resulting in unstable quality. Moreover, the composition of liquor changes relatively slowly during the natural aging process, making it difficult to accurately predict and adjust, making it difficult for the taste and aroma of liquor to reach an ideal state.
[0005] In addition, traditional aging methods still have certain limitations. For example, during the natural aging process, some harmful substances in the liquor may not be completely removed, affecting the safety of the liquor. At the same time, natural aging may not be effective for some new liquors or liquors with special flavors, and cannot meet consumers' demand for diversified liquor products.
[0006] In order to solve these problems of traditional liquor aging methods, researchers have been exploring new aging technologies and methods. In recent years, with the rapid development of nanotechnology, the application of nanomaterials in various fields has become more and more extensive. In the field of liquor aging, nanomaterials have also shown great potential.
[0007] Nanomaterials have unique physical and chemical properties such as high specific surface area, special surface activity and quantum size effect. These properties enable nanomaterials to fully contact with various components in liquor, adsorb and catalyze chemical reactions therein, thereby accelerating the aging process of liquor. For example, some nanomaterials can absorb impurities and odors in liquor, improving the purity and taste of liquor; other nanomaterials can catalyze reactions such as esterification and oxidation in liquor, promote the generation of aroma substances, and make the aroma of liquor more intense.
[0008] However, the application of nanomaterials in liquor aging is still facing some challenges. On the one hand, the selection and preparation of nanomaterials need to take into account their compatibility with liquor, stability and safety. Inappropriate nanomaterials may have a negative impact on the quality of liquor and even endanger the health of consumers. On the other hand, how to effectively apply nanomaterials to the liquor aging process is also a key issue. Simply adding nanomaterials to liquor may cause the agglomeration and precipitation of nanomaterials, affecting their effect.
[0009] In order to better play the role of nanomaterials in liquor aging, it is particularly important to design a special loading tank. The loading tank can provide a stable carrier and working environment for nanomaterials, ensure that nanomaterials are in full contact with liquor, and prevent the loss and contamination of nanomaterials. By optimizing the structure and parameters of the loading tank, factors such as the contact time, temperature and pressure between nanomaterials and liquor can be controlled, thereby achieving precise regulation of the liquor aging process.
[0010] In summary, the traditional natural aging method of liquor has problems such as time-consuming, difficult to control the effect and limitations, and the application of nanomaterials and their loading tanks provides a new idea and method to solve these problems. The development of a liquor aging technology based on nanomaterials and their loading tanks has important practical significance for improving the production efficiency of liquor, ensuring stable quality and meeting market demand. Summary of the invention
[0011] In order to solve the above problems, especially to address the deficiencies in the prior art, the present invention provides a nano material and a feeding tank thereof for use in liquor aging, which can solve the above problems.
[0012] To achieve the above purpose, the present invention adopts the following technical means:
[0013] An application of nanomaterials in liquor aging comprises the following steps:
[0014] Step 1, 6-8% silicon dioxide, 7-9% nano titanium dioxide, 5-10% nano aluminosilicate, 4-6% aluminum oxide, 5-7% nano zinc oxide, 5-7% nano cerium oxide, 4-6% zirconium oxide, 6-8% nano montmorillonite, 6-8% nano tourmaline, 6-8% magnesium oxide, 7-9% nano activated carbon, 4-6% nano barium titanate, 9-11% polyvinyl chloride powder, 3-5% chitosan nanoparticles, and 3-5% nano cellulose are mixed, and PVC particles are prepared by conventional methods to obtain the desired nano material;
[0015] Step 2: Calculate the amount of nanomaterials based on the volume of the wine storage tank;
[0016] Step 3: Add the nanomaterials in groups to the feeding tank and put them into the original wine stored in the wine storage tank;
[0017] Step 4: Stir regularly and age for 30-60 days.
[0018] A further solution of the present invention is that the weight percentages of the nanomaterial composition in step one are as follows: 6% silicon dioxide, 7% nano titanium dioxide, 8% nano aluminosilicate, 5% aluminum oxide, 6% nano zinc oxide, 6% nano cerium oxide, 6% zirconium oxide, 6% nano montmorillonite, 6% nano tourmaline, 8% magnesium oxide, 9% nano activated carbon, 6% nano barium titanate, 11% polyvinyl chloride powder, 5% chitosan nanoparticles, and 5% nano cellulose.
[0019] A further solution of the present invention is that the weight percentages of the nanomaterial composition in step one are as follows: 8% silicon dioxide, 7% nano titanium dioxide, 8% nano aluminosilicate, 4% aluminum oxide, 5% nano zinc oxide, 6% nano cerium oxide, 5% zirconium oxide, 7% nano montmorillonite, 7% nano tourmaline, 7% magnesium oxide, 9% nano activated carbon, 6% nano barium titanate, 11% polyvinyl chloride powder, 5% chitosan nanoparticles, and 5% nano cellulose.
[0020] A further solution of the present invention is that the weight percentages of the nanomaterial composition in step one are as follows: 8% silicon dioxide, 9% nano titanium dioxide, 9% nano aluminosilicate, 6% aluminum oxide, 5% nano zinc oxide, 5% nano cerium oxide, 6% zirconium oxide, 7% nano montmorillonite, 7% nano tourmaline, 7% magnesium oxide, 8% nano activated carbon, 5% nano barium titanate, 10% polyvinyl chloride powder, 4% chitosan nanoparticles, and 4% nano cellulose.
[0021] A further solution of the present invention is that the mass ratio of the amount of the nano material used in step 2 to the amount of the original wine is 1-2kg:800kg.
[0022] A feeding tank used in the application of nanomaterials in liquor aging, comprising a fixed seat, a transmission motor is connected to the top of the fixed seat, a transmission end of the transmission motor is connected to a transmission rod penetrating the fixed seat, and the transmission rod is transmission-connected to multiple groups of tank components equidistantly distributed above and below;
[0023] The material tank assembly includes a material tank, which is provided with multiple groups of evenly distributed liquid permeable holes. The openings at both ends of the material tank are detachably connected with sealing covers, and the middle part of the sealing cover is inlaid with a directional groove ring. A rotating ring is connected to the ring groove of the directional groove ring through ball rotation. A sleeve is connected to the rotating ring. The sleeve is sleeved on the outside of the transmission rod and fixedly connected to the transmission rod through a fixing wire. A stirring blade connected to the transmission rod is provided in the material tank.
[0024] A further solution of the present invention is that a connecting ring is sleeved on the outer side of the sealing cover, and the connecting ring is threadedly connected with a positioning rod that can be positioned and connected to an external structure.
[0025] A further solution of the present invention is that a feeding port is provided on the top of the sealing cover close to the transmission motor, a feeding funnel is connected to the outside of the feeding port, and a sealing cover is detachably connected to the feeding port of the feeding funnel.
[0026] A further solution of the present invention is that the top of the sealing cover is a convex structure.
[0027] A further solution of the present invention is that the rotating ring and the sleeve are made in one piece.
[0028] Silica: Silica plays a certain structural support and adsorption role in nanomaterials, which may affect the adsorption and reaction of some components in liquor, thereby having a positive impact on the aging process.
[0029] Nano titanium dioxide: Nano titanium dioxide has photocatalytic properties. Under certain conditions, it can promote the oxidation reaction of certain components in liquor, accelerate the aging process, and also absorb some impurities.
[0030] Nano-aluminosilicate: Nano-aluminosilicate has good adsorption properties and can absorb harmful components such as fusel oil and aldehydes in liquor. At the same time, it can provide active sites for catalysis for some beneficial reactions in liquor.
[0031] Alumina: Alumina has high stability and adsorption properties. It can absorb some impurities and odorous substances in liquor, helping to improve the quality and taste of liquor.
[0032] Nano zinc oxide: Nano zinc oxide has antibacterial and odor-absorbing effects, which can help remove bad odors in liquor and improve the purity of liquor.
[0033] Nano-cerium oxide: Nano-cerium oxide has certain redox properties and can participate in the redox reaction in liquor, promoting the formation and transformation of flavor substances in liquor.
[0034] Zirconium oxide: Zirconium oxide can increase the hardness and stability of nanomaterials. It may participate in some physical or chemical effects during the aging process of liquor and promote the aging of liquor.
[0035] Nano-montmorillonite: Nano-montmorillonite has good adsorption properties and can absorb some harmful substances and impurities in liquor. It can also adjust the pH value of liquor and has a positive effect on aging.
[0036] Nano-tourmaline: Nano-tourmaline can release negative ions and far infrared rays, which may affect the molecular structure of liquor and accelerate the reaction between molecules and the aging process.
[0037] Magnesium oxide: Magnesium oxide has a certain alkalinity and may react with the acidic substances in the liquor to adjust the pH of the liquor, thereby affecting the taste and flavor of the liquor.
[0038] Nano-activated carbon: Nano-activated carbon has extremely high specific surface area and adsorption capacity, which can absorb odors, impurities and some unstable components in liquor, making the liquor purer and mellower in taste.
[0039] Nano-barium titanate: Nano-barium titanate has certain piezoelectric properties and may interact with the molecules in the liquor under certain conditions to promote the aging reaction.
[0040] Polyvinyl chloride powder: As a polymer material, polyvinyl chloride powder can combine other nano-scale powder materials together to form stable nano-material particles, which are convenient for use in liquor.
[0041] Chitosan nanoparticles: Chitosan nanoparticles have certain antibacterial and adsorption properties, which can help remove harmful components in liquor and may have a certain regulatory effect on the flavor of liquor.
[0042] Nanocellulose: Nanocellulose can be used as a carrier to evenly disperse other nanomaterials in liquor, and it may also have a certain positive effect on the taste and stability of liquor.
[0043] Beneficial effects of the present invention:
[0044] 1. The nanomaterial of the present invention has an adsorption effect. The nanomaterial has an extremely high specific surface area and special surface activity, and can adsorb impurities and odors in liquor, such as aldehydes, ketones, fusel oils, etc. Through adsorption, the nanomaterial can remove undesirable components in liquor and improve the purity and taste of liquor. At the same time, the nanomaterial can also adsorb aroma components in liquor, such as esters, alcohols, etc., so that they are enriched on the surface of the nanomaterial, increasing the concentration and stability of the aroma.
[0045] 2. The nanomaterials of the present invention have catalytic effects. Nanomaterials can be used as catalysts to accelerate chemical reactions in liquor, such as esterification, oxidation, and condensation reactions. For example, nano metal oxides can catalyze the esterification of alcohols and acids in liquor to generate more esters, thereby improving the aroma and taste of liquor. Nano carbon materials can catalyze oxidation reactions in liquor, remove odors and impurities, and improve the purity of liquor.
[0046] 3. The nanomaterials of the present invention have a diffusion effect. The small size effect of the nanomaterials accelerates their diffusion speed in the liquor, which can promote the diffusion and mixing of molecules in the liquor. The nanomaterials can serve as diffusion channels, making it easier for the various components in the liquor to contact and react with each other, accelerating the aging process. At the same time, the nanomaterials can also change the microstructure of the liquor, increase its porosity and permeability, and improve the diffusion efficiency of the molecules.
[0047] 4. The feeding tank of the present invention can provide a stable working environment for nanomaterials. The feeding tank can provide a stable working environment for nanomaterials to prevent the nanomaterials from being affected by external factors such as light, temperature, humidity, etc. At the same time, the feeding tank can also prevent the loss and agglomeration of nanomaterials, ensuring their stability and effectiveness during the aging process of liquor.
[0048] 5. The feeding tank of the present invention can realize the reuse of nano materials. The feeding tank can conveniently separate the nano materials from the liquor, clean and regenerate them, and realize the reuse of the nano materials. This can not only reduce production costs, but also reduce pollution to the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 It is a structural schematic diagram of the feeding tank of the present invention;
[0050] Figure 2 It is a structural schematic diagram of the transmission rod of the present invention;
[0051] Figure 3 is a cross-sectional view of a tank assembly of the present invention;
[0052] Reference numerals:
[0053] Material tank assembly 1, positioning rod 2, transmission rod 3, fixing seat 4, transmission motor 5, stirring blade 6, connecting ring 101, sealing cover 102, feeding funnel 103, blocking cover 104, feeding port 105, rotating ring 106, sleeve 107, ball 108, directional groove ring 109, liquid permeable hole 110, material tank 111. DETAILED DESCRIPTION
[0054] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Example 1
[0056] An application of nanomaterials in liquor aging comprises the following steps:
[0057] Step 1, 6% silicon dioxide, 7% nano titanium dioxide, 8% nano aluminosilicate, 5% aluminum oxide, 6% nano zinc oxide, 6% nano cerium oxide, 6% zirconium oxide, 6% nano montmorillonite, 6% nano tourmaline, 8% magnesium oxide, 9% nano activated carbon, 6% nano barium titanate, 11% polyvinyl chloride powder, 5% chitosan nanoparticles, and 5% nano cellulose are mixed, and PVC particles are prepared by conventional methods to obtain the desired nano material;
[0058] Step 2: Calculate the amount of nanomaterials based on the volume of the wine storage tank. The mass ratio of the amount of nanomaterials to the amount of original wine is 1kg:800kg.
[0059] Step 3: Add the nanomaterials in groups to the feeding tank and put them into the original wine stored in the wine storage tank;
[0060] Step 4: Stir regularly and age for 30 days.
[0061] Example 2
[0062] An application of nanomaterials in liquor aging comprises the following steps:
[0063] Step 1, 8% silicon dioxide, 7% nano titanium dioxide, 8% nano aluminosilicate, 4% aluminum oxide, 5% nano zinc oxide, 6% nano cerium oxide, 5% zirconium oxide, 7% nano montmorillonite, 7% nano tourmaline, 7% magnesium oxide, 9% nano activated carbon, 6% nano barium titanate, 11% polyvinyl chloride powder, 5% chitosan nanoparticles, and 5% nano cellulose are mixed, and PVC particles are prepared by conventional methods to obtain the desired nano material;
[0064] Step 2: Calculate the amount of nanomaterials based on the volume of the wine storage tank. The mass ratio of the amount of nanomaterials to the amount of original wine is 1kg:800kg.
[0065] Step 3: Add the nanomaterials in groups to the feeding tank and put them into the original wine stored in the wine storage tank;
[0066] Step 4: Stir regularly and age for 40 days.
[0067] Example 3
[0068] An application of nanomaterials in liquor aging comprises the following steps:
[0069] Step 1: 8% silicon dioxide, 9% nano titanium dioxide, 9% nano aluminosilicate, 6% aluminum oxide, 5% nano zinc oxide, 5% nano cerium oxide, 6% zirconium oxide, 7% nano montmorillonite, 7% nano tourmaline, 7% magnesium oxide, 8% nano activated carbon, 5% nano barium titanate, 10% polyvinyl chloride powder, 4% chitosan nanoparticles, and 4% nano cellulose are mixed and made into PVC particles by conventional methods to obtain the desired nano material;
[0070] Step 2: Calculate the amount of nanomaterials based on the volume of the wine storage tank. The mass ratio of the amount of nanomaterials to the amount of original wine is 1kg:400kg.
[0071] Step 3: Add the nanomaterials in groups to the feeding tank and put them into the original wine stored in the wine storage tank;
[0072] Step 4: Stir regularly and age for 60 days.
[0073] Example 4
[0074] like Figure 1-3 As shown, a feeding tank used in the application of nanomaterials in liquor aging includes a fixed seat 4, a transmission motor 5 is connected to the top of the fixed seat 4, a transmission end of the transmission motor 5 is connected to a transmission rod 3 that penetrates the fixed seat 4, and the transmission rod 3 is transmission-connected to multiple groups of material tank components 1 that are evenly distributed up and down;
[0075] The material tank assembly 1 includes a material tank 111, which is provided with a plurality of groups of evenly distributed liquid permeable holes 110. The openings at both ends of the material tank 111 are detachably connected with sealing covers 102. The middle part of the sealing cover 102 is inlaid with a directional groove ring 109. A rotating ring 106 is rotatably connected in the ring groove of the directional groove ring 109 through a ball 108. A sleeve 107 is connected in the rotating ring 106. The sleeve 107 is sleeved on the outside of the transmission rod 3 and fixedly connected to the transmission rod 3 through a fixing wire. A stirring blade 6 connected to the transmission rod 3 is provided in the material tank 111.
[0076] The outer side of the sealing cover 102 is sleeved with a connecting ring 101, and the connecting ring 101 is threadedly connected with a positioning rod 2 that can be positioned and connected to the external structure. This arrangement can prevent the transmission rod 3 from rotating during the transmission process of the material tank 111, and effectively improve the stability of the material tank 111 during use.
[0077] A feeding port 105 is provided at the top of the sealing cover 102 near the transmission motor 5, and a feeding funnel 103 is connected to the outside of the feeding port 105, and a plugging cover 104 is detachably connected to the feeding port of the feeding funnel 103. This arrangement can facilitate the user to add nanomaterials into the material tank 111, effectively improving the working efficiency and working effect of the material tank 111.
[0078] The top of the blocking cover 104 is an outward convex structure. This arrangement can facilitate the user to disassemble the blocking cover 104, effectively improving the working efficiency and working effect of the blocking cover 104.
[0079] The rotating ring 106 and the sleeve 107 are made in one piece. This arrangement can ensure tightness between the rotating ring 106 and the sleeve 107, and can effectively prevent the rotating ring 106 and the sleeve 107 from separating.
[0080] How it works
[0081] The transmission motor 5 is connected to the sealing cover of the aging tank through the fixing base 4;
[0082] The material tank assembly 1 is connected to the transmission rod 3. The specific connection method is as follows: first, the sleeve 107 of the sealing cover 102 with the feeding port 105 is sleeved on the transmission rod 3 and fixedly connected to the transmission rod 3 through a fixing wire. Then, a plurality of groups of stirring blades 6 connected to the transmission rod 3 are installed at the bottom of the sealing cover 102 with the feeding port 105. The transmission rod 3 is sleeved on the material tank 111. The material tank 111 covers all the stirring blades 6 and is connected to the sealing cover 102 with the feeding port 105. Finally, the sleeve 107 of the sealing cover 102 without the feeding port 105 is sleeved on the transmission rod 3. The sealing cover 102 without the feeding port 105 is connected to the material tank 111 and is also fixedly connected to the transmission rod 3 through a fixing wire.
[0083] After the material tank assembly 1 is connected to the transmission rod 3, the weighed nanomaterials are added into the storage space composed of two sets of sealing covers 102 and one set of material tanks 111 through the feeding funnel 103;
[0084] After the feeding is completed, the transmission rod 3 is inserted into the aging tank and passes through the sealing cover of the aging tank to be connected with the transmission motor 5;
[0085] The nano material in the tank assembly 1 contacts with the wine in the aging tank for aging. During the aging process, the transmission motor 5 is started, and the transmission motor 5 drives the stirring blade 6 to stir the nano material in the tank assembly 1, so that the nano material contacts with the wine more evenly.
[0086] Example 5
[0087] A control group and experimental groups with different gradient dosages of nanomaterials were set up to test 62° light-fragrance base liquor. By monitoring the dynamic changes of aging of each component in the base liquor, the optimal addition treatment amount and the shortest treatment time equivalent to natural aging were found, as shown in Table 1.
[0088] Table 1 Amount of nanomaterials used
[0089]
[0090] Example 6
[0091] The number of feeding tanks was calculated based on the volume of the original wine storage tanks of the wine company (one feeding tank for one ton of original wine), and then the feeding tanks filled with nanomaterials were placed in different original wine storage tanks (other parameters of the original wine were the same). Wine samples were collected from the original wine tanks at 1d, 7d, 15d, 30d and 45d of the control group and the experimental group, and the alcohol content, fusel oil, methanol, total aldehyde, total acid and total ester of the wine samples were dynamically monitored according to GB / T10345-2007. The saved data were compared with the relevant indicators of the naturally aged wine samples of the same batch of liquor for one year to determine the effect of nanomaterials on the accelerated aging of liquor, as shown in Table 2.
[0092] Table 2 Test results of relevant indicators
[0093] index Alcohol content Fusel Oil Methanol Total aldehyde Total acid Total esters Control group (original wine) 62° 0.14g / 100ml 0.04g / 100ml 0.02g / 100ml 0.06g / 100ml 0.03g / 100ml Experimental Group 1 62° 0.09g / 100ml 0.02g / 100ml 0.18g / 100ml 0.10g / 100ml 0.07g / 100ml Experimental Group 2 62° 0.07g / 100ml 0.02g / 100ml 0.15g / 100ml 0.12g / 100ml 0.08g / 100ml Experimental Group 3 62° 0.05g / 100ml 0.02g / 100ml 0.14g / 100ml 0.14g / 100ml 0.09g / 100ml Natural aging (1 year) 62° 0.07g / 100ml 0.03g / 100ml 0.14g / 100ml 0.14g / 100ml 0.08g / 100ml
[0094] The above-mentioned testing indicators, alcohol content, fusel oil, methanol, total aldehydes, total acids and total esters are measured based on GB / T10345-2007 “Analysis Method for Liquor”.
[0095] The examples given in the present invention are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. An application of nanomaterials in liquor aging, characterized in that: The following steps are involved: Step 1, 6-8% silicon dioxide, 7-9% nano titanium dioxide, 5-10% nano aluminosilicate, 4-6% aluminum oxide, 5-7% nano zinc oxide, 5-7% nano cerium oxide, 4-6% zirconium oxide, 6-8% nano montmorillonite, 6-8% nano tourmaline, 6-8% magnesium oxide, 7-9% nano activated carbon, 4-6% nano barium titanate, 9-11% polyvinyl chloride powder, 3-5% chitosan nanoparticles, and 3-5% nano cellulose are mixed, and PVC particles are prepared by conventional methods to obtain the desired nano material; Step 2: Calculate the amount of nanomaterials based on the volume of the wine storage tank; Step 3: Add the nanomaterials in groups to the feeding tank and put them into the original wine stored in the wine storage tank; Step 4: Stir regularly and age for 30-60 days.
2. The use of the nanomaterial in liquor aging according to claim 1, characterized in that: The weight percentages of the nanomaterial composition in step one are as follows: 6% silicon dioxide, 7% nano titanium dioxide, 8% nano aluminosilicate, 5% aluminum oxide, 6% nano zinc oxide, 6% nano cerium oxide, 6% zirconium oxide, 6% nano montmorillonite, 6% nano tourmaline, 8% magnesium oxide, 9% nano activated carbon, 6% nano barium titanate, 11% polyvinyl chloride powder, 5% chitosan nanoparticles, and 5% nano cellulose.
3. The use of the nano material in liquor aging according to claim 1, characterized in that: The weight percentages of the nanomaterial composition in step one are as follows: 8% silicon dioxide, 7% nano titanium dioxide, 8% nano aluminosilicate, 4% aluminum oxide, 5% nano zinc oxide, 6% nano cerium oxide, 5% zirconium oxide, 7% nano montmorillonite, 7% nano tourmaline, 7% magnesium oxide, 9% nano activated carbon, 6% nano barium titanate, 11% polyvinyl chloride powder, 5% chitosan nanoparticles, and 5% nano cellulose.
4. The use of the nano material in liquor aging according to claim 1, characterized in that: The weight percentages of the nanomaterial composition in step one are as follows: 8% silicon dioxide, 9% nano titanium dioxide, 9% nano aluminosilicate, 6% aluminum oxide, 5% nano zinc oxide, 5% nano cerium oxide, 6% zirconium oxide, 7% nano montmorillonite, 7% nano tourmaline, 7% magnesium oxide, 8% nano activated carbon, 5% nano barium titanate, 10% polyvinyl chloride powder, 4% chitosan nanoparticles, and 4% nano cellulose.
5. The use of the nano material in liquor aging according to claim 1, characterized in that: The mass ratio of the amount of the nano material used in step 2 to the amount of the original wine is 1-2kg:800kg.
6. A feeding tank used in the application of the nanomaterial described in claim 1 in the aging of liquor, characterized in that: It comprises a fixed seat (4), the top of the fixed seat (4) is connected to a transmission motor (5), the transmission end of the transmission motor (5) is connected to a transmission rod (3) that passes through the fixed seat (4), and the transmission rod (3) is transmission-connected to a plurality of groups of material tank assemblies (1) that are equidistantly distributed up and down; The material tank assembly (1) comprises a material tank (111), wherein the material tank (111) is provided with a plurality of groups of evenly distributed liquid permeable holes (110), and the openings at both ends of the material tank (111) are respectively detachably connected to sealing covers (102), and a directional groove ring (109) is embedded and connected in the middle of the sealing cover (102), and a rotating ring (106) is rotatably connected in the ring groove of the directional groove ring (109) via a ball (108), and a sleeve (107) is connected in the rotating ring (106), and the sleeve (107) is sleeved on the outside of a transmission rod (3) and fixedly connected to the transmission rod (3) via a fixing wire, and a stirring blade (6) connected to the transmission rod (3) is arranged in the material tank (111).
7. The feeding tank used in the application of the nano material in liquor aging according to claim 6 is characterized in that: A connecting ring (101) is sleeved on the outer side of the sealing cover (102), and the connecting ring (101) is threadedly connected to a positioning rod (2) capable of being positioned and connected to an external structure.
8. The feeding tank used in the application of the nano material in liquor aging according to claim 6 is characterized in that: A feeding port (105) is provided at the top of the sealing cover (102) near the transmission motor (5), a feeding funnel (103) is connected to the outside of the feeding port (105), and a blocking cover (104) is detachably connected to the feeding port of the feeding funnel (103).
9. The feeding tank used in the application of the nano material in liquor aging according to claim 8, characterized in that: The top of the blocking cover (104) is an outward convex structure.
10. The feeding tank used in the application of the nano material in liquor aging according to claim 6, characterized in that: The rotating ring (106) and the sleeve (107) are made in one piece.